2012
DOI: 10.1016/j.jcat.2012.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat treatment on the performance and structure of carbon-supported Au–Pd catalysts for the direct synthesis of hydrogen peroxide

Abstract: a b s t r a c tThe direct synthesis of hydrogen peroxide using supported gold palladium catalysts prepared by incipient wetness impregnation is described and discussed. The effect of an acid pre-treatment step on the activated carbon support prior to the deposition of the metals, together with the effect of the calcination temperature, has been investigated. The acid pre-treated samples all show superior activity to those materials prepared with the omission of this acid pre-treatment stage. The calcination te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 17 publications
8
89
0
Order By: Relevance
“…It was reported by Landon et al 47,130 that the addition of small amounts of Au or Pt to Pd leads to a significant enhancement, especially in terms of selectivity in the hydrogen peroxide direct synthesis; however, sometimes the same trend was also observed for the hydrogenation of the hydrogen peroxide that was formed. This effect has been subsequently confirmed in many studies by Edwards et al 50,93,120,124,126 , Bernardotto et al, 92 Menegazzo et al 44,113 and Hutchings et al 125 Notwithstanding, the combination of bimetallic catalysts with a proper acidified support leads to a decrease of the hydrogenation reaction. It is interesting to see that the addition of Au or Pt improves the selectivity while at the same time reducing the rate of H 2 conversion.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…It was reported by Landon et al 47,130 that the addition of small amounts of Au or Pt to Pd leads to a significant enhancement, especially in terms of selectivity in the hydrogen peroxide direct synthesis; however, sometimes the same trend was also observed for the hydrogenation of the hydrogen peroxide that was formed. This effect has been subsequently confirmed in many studies by Edwards et al 50,93,120,124,126 , Bernardotto et al, 92 Menegazzo et al 44,113 and Hutchings et al 125 Notwithstanding, the combination of bimetallic catalysts with a proper acidified support leads to a decrease of the hydrogenation reaction. It is interesting to see that the addition of Au or Pt improves the selectivity while at the same time reducing the rate of H 2 conversion.…”
mentioning
confidence: 66%
“…131 The synergetic behaviour of the two metals is usually considered to originate from an electronic effect rather than from a morphological effect, but the precise origin is yet to be determined. 44,92,113,124 Since there are no significant differences in the particle size distribution and particle morphology for these Au-Pd nanoalloy catalysts prepared using different Pd/Au ratios, it is believed, based on the results published in recent years, that the positive effects observed when alloying Pd and Au are caused by an electronic effect where the addition of a small amount of Au affects the electronic nature of Pd. 125,126 However, other authors found that the effect can be ascribed to both the effects: morphological and electronic.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The main issue is still the design of appropriated catalysts [5] (active metal or support [6][7][8][9][10][11][12][13][14][15][16][17]), followed by the focus on the addition of promoters (acids and halides) [6,11,16,17], selection of liquid solvent (water, methanol, ethanol or a mixture of them) and optimization of reaction conditions since appropriate selection of operational parameters are crucial in aiming at high selectivities in the H 2 O 2 direct synthesis [18][19][20][21][22][23][24][25][26][27][28][29]. Finally, the gas phase concentration is limited by flammability limits of hydrogen-oxygen mixtures.…”
Section: Introductionmentioning
confidence: 99%